Enhancement of hemispherical solar still productivity using iron, zinc and copper trays. (1st March 2021) - Attia, Mohammed El Hadi; Kabeel, A.E.; Abdelgaied, Mohamed; Essa, F.A.; Omara, Z.M.
Graphical abstract: Highlights: Hemispherical solar still of different metal trays is investigated. Three types of trays (copper (THSSC), zinc (THSSZ), and iron (THSSI)) were studied. THSSI containing the iron tray was about 1.17 times the daily productivity of CHSS. THSSC with copper structure showed 53.125% increase in productivity compared to CHSS. Thermal efficiency of CHSS, THSSI, THSSZ and THSSC were 37.4%, 42.8%, 49% and 57.2%, respectively. Abstract: In this manuscript, a hemispherical solar still with different metal trays (copper, zinc, and iron) painted with black was studied experimentally. Four hemispherical solar stills were manufactured; the first is the conventional hemispherical solar still which represent the reference case (CHSS), the second, third and fourth were the modified hemispherical solar stills with adding black metal trays of copper, zinc, and iron, respectively. These trays were placed at the bottom of the distiller basin. This modification led to a significant increase in the rate of evaporation of the salt water in the distiller basin due to the improved heat transfer characteristics. The basin water depth in the trays are kept constant at 10 mm in all experiments. The results showed that the accumulative yield of the hemispherical solar still reached to 4.8 kg/m 2 /day, while the utilization of iron, zinc and copper trays improved the accumulative yield to 5.5, 6.3 and 7.35 kg/m 2 /day, respectively. These results presented that the trays hemispherical solar still of iron (THSSI) was about 1.17 times the daily productivity of CHSS, while trays hemispherical solar still of zinc (THSSZ) showed an increase in productivity by 31.25% compared to CHSS. Moreover, the trays hemispherical solar still of copper (THSSC) gave improved productivity by 53.125% compared to CHSS. The thermal efficiency of CHSS, THSSI, THSSZ and THSSC were 37.4%, 42.8%, 49% and 57.2%, respectively.